2014
DOI: 10.18357/ijcyfs.ohlmannc.512014
|View full text |Cite
|
Sign up to set email alerts
|

Listening for the Voices of Resilience: A Group of Adolescents’ Experiences With a Suicide Prevention Education Program

Abstract: Adolescents' experiences in a grassroots, school-based suicide prevention education group in British Columbia, Canada, were investigated in response to anecdotal observations of the group's strong positive impact. In the Alive group, at-risk high school students, 15 to 18 years of age, learned to support each other, became literate in mental health issues, and created and performed presentations on suicide prevention to peers. The authors employed the qualitative method of the Listening Guide to explore the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The analysis shows that CCI contributes to enhanced help-seeking attitudes and knowledge, as well as perceived positive connections and skill-building. The study is in line with research that shows that peer leadership GKT can be beneficial for those who are involved as youth leaders (Ohlmann et al, 2014;Walker et al, 2009;Wasserman et al, 2012;Wyman et al, 2010). Uniquely, this study demonstrated the potential benefit of utilizing a critical pedagogical approach to youth mental health literacy and promotion and may have implications for other programs.…”
Section: Implications and Programmatic Changessupporting
confidence: 85%
See 1 more Smart Citation
“…The analysis shows that CCI contributes to enhanced help-seeking attitudes and knowledge, as well as perceived positive connections and skill-building. The study is in line with research that shows that peer leadership GKT can be beneficial for those who are involved as youth leaders (Ohlmann et al, 2014;Walker et al, 2009;Wasserman et al, 2012;Wyman et al, 2010). Uniquely, this study demonstrated the potential benefit of utilizing a critical pedagogical approach to youth mental health literacy and promotion and may have implications for other programs.…”
Section: Implications and Programmatic Changessupporting
confidence: 85%
“…Furthermore, there are potential limitations to adult gatekeepers, as youth are more likely to confide in their peers about distressing issues and typically seek help from their peers (Gilchrist & Sullivan, 2006;Smith et al, 2019). (Walker et al, 2009), Sources of Strength (Wyman et al, 2010), Saving and Empowering Young Lives in Europe (SEYLE) Awareness program (Wasserman et al, 2012), and, in Canada, the Alive group (also known as Youth as Gatekeepers; Ohlmann et al, 2014;Wicker, 2012). These peer GKT programs show positive benefits for the youth peer leaders who are involved in them, including "a significant increase in knowledge and positive attitudes towards suicide prevention, and also self-esteem" (Walker et al, 2009, p. 335), enhanced knowledge about mental health (Wasserman et al, 2012), increased positive coping and connection to adults (Wyman et al, 2010), and perceived interpersonal resilience (Ohlmann et al, 2014).…”
Section: Peer Gatekeeper-training and Positive Youth Developmentmentioning
confidence: 99%
“…It is not always clear why the I poems have been omitted in the write-up. Occasionally researchers note that I poems were constructed during analysis, but not included in the write-up that was eventually published (e.g., Kayser, Watson, & Andrade, 2007; Ohlmann, Kwee, & Lees, 2014). In instances when the I poems have not been constructed at all, however, the “opportunity to attend to just the sounds, rhythms, and shifts in [the participant’s] usages of ‘I’ in his or her narrative” (Gilligan et al, 2003) has been lost.…”
Section: The Listening Guide and I Poemsmentioning
confidence: 99%
“…Arts-in-health research, however, requires unique interdisciplinary research teams, methodology and project evaluation (Artreach Toronto, 2018;Broderick, 2011;Daykin, Attwood, & Willis, 2013;Fancourt & Joss, 2014;Guetzkow, 2002;Marcuse et al, 2016). Games-based interventions using improvisation encourage participants to express emotions and share personal stories, fostering relationships, resilience and hope (Andersson & Ledogar, 2008;Ohlmann, Kwee, & Lees, 2014). In short, research outlines the ways in which arts-based and participatory methods are effective methods.…”
Section: Introductionmentioning
confidence: 99%